Triatoma brasiliensis species complex: characterization of the external female genitalia - de Oliveira, Jader [UNESP]; Chaboli Alevi, Kaio Cesar [UNESP]; Almeida, Carlos Eduardo; Mendonça, Vagner José; Costa, Jane; da Rosa, João Aristeu [UNESP] (Society for Vector Ecology, 2020)
The Triatoma brasiliensis complex is composed of six species (Triatoma bahiensis, T. juazerensis, T. lenti, T. melanica, T. petrocchiae, and T. sherlocki) and two subspecies (T. brasiliensis brasiliensis and T. b. macromelasoma). Phylogenetic studies have shown that it is a monophyletic group, but the morphological relationships among the members can be better understood. We applied a tool of high resolution based on morphology to identify details that characterize the female genitals for each member of this group. The external genital structures of five to fifteen females of each taxon were analyzed. Insects had their abdomen transversely cut to separate the last abdominal segments, and representative illustrations obtained via scanning electron microscopy (SEM) are shown. Observations were performed in the dorsal and the ventral views. The morphological characterization of female external genitalia allowed a differentiation of each species/subspecies. The subspecies T. b. brasiliensis and T. b. macromelasoma were the most similar. On the other hand, dorsal view of structures evidenced some unique characteristics for T. petrocchiae and T. sherlocki. Regarding these structures for T. petrocchiae, the differentiation was in accordance with molecular studies, since this species exhibits the highest genetic distances in relation to other species of T. brasiliensis complex.
Keywords: Chagas disease vectors; morphology; Systematics